TEMPOROMANDIBULAR DISORDERS AND EXERCISES APPROACHES: TMD and exercise - Baykan Çopuroglu, Özge; Özden YA?ARER (Innovative Journal of Medical and Health Sciences, 2022)
Temporomandibular disorder (TMD); It is a common clinical problem that affects the masticatory muscles, temporomandibular joint (TMJ), and one or more of the hard and soft tissues adjacent to the temporomandibular joint, characterized by pain in the temporomandibular joint and/or masticatory muscles, irregularity in mandibular movements, clicking, popping sound and/or crepitation in the joint.